ABOUT THE FACTORS HAMPERING THE INNOVATIVE ACTIVITY OF RUSSIAN ENTREPRENEURSHIP - Mariya Mankaeva; Tatiana Pogodina (Вестник Северо-Кавказского федерального университета, 2022)
Adoption of a number ofnormative documents defining the tasks of the innovative orientation of Russia's economic development, necessitates the identification of factors hindering the innovation activity of economic entities. Despite the availability of statistical data on indicators of innovation activity and factors hampering innovation, it is necessary to conduct their analysis, systematization, identify the most significant factors for different types of economic activity and regions in order to determine the priority of measures to neutralize them. Proceeding from this, the study offactors hampering the innovative activity of Russian entrepreneurship, and the development of proposals for their neutralization, is of major economic importance. The article considers the main factors hampering innovation activity. Carry out an analysis of statistical data related to these factors.